Familial Hypercholesterolemia: a Review of the Natural History, Diagnosis, and Management - Najam, Osman (Cardiol Ther, 2015)
Familial hypercholesterolemia (FH) is an inherited disorder of lipid metabolism characterized by premature cardiovascular disease. It is one of the most common metabolic disorders affecting humans. There are two clinical manifestations: the milder heterozygous form and more severe homozygous form. Despite posing a significant health risk, FH is inadequately diagnosed and managed. As the clinical outcome is related to the degree and duration of exposure to elevated low-density lipoprotein cholesterol (LDL-C) levels, early treatment is vital. Diagnosis can usually be made using a combination of clinical characteristics such as family history, lipid levels, and genetic testing. Mutations in the gene encoding the LDL receptor (LDLR), apolipoprotein B, the pro-protein convertase subtilisin/kexin 9 (PCSK9), and LDLR adaptor protein are the commonest abnormalities. Early identification and treatment of patients, as well as screening of relatives, helps significantly reduce the risk of premature disease. Although statins remain the first-line therapy in most cases, monotherapy is usually inadequate to control elevated LDL-C levels. Additional therapy with ezetimibe and bile acid sequestrants may be required. Newer classes of pharmacotherapy currently under investigation include lomitapide, mipomersen, and monoclonal antibodies to PCSK9. Lipoprotein apheresis may be required when multiple pharmacotherapies are inadequate, especially in the homozygous form. Effective early detection and treatment of the index individual and initiation of cascade screening will help reduce the complications associated with FH. In this article, we review the disease of FH, complexity of diagnosis and management, and the challenges faced in preventing the significant morbidity and mortality associated with it. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s40119-015-0037-z) contains supplementary material, which is available to authorized users.